The Chemical Composition and Biological Activities of Essential Oil from Korean Native Thyme Bak-Ri-Hyang (Thymus quinquecostatus Celak.) - Minju Kim; Kandhasamy Sowndhararajan; Songmun Kim (Molecules, 2022)
Thymus quinquecostatus Celak. (Korean name: bak-ri-hyang) is an important medicinal and aromatic herb in Korea, which is named for the spread of its fragrance over a distance of approximately 40 km. In traditional Korean systems of medicine, T. quinquecostatus has been used to treat cancer, constipation, hepatic disease, arteriosclerosis, poor circulation in women, constipation, and menstrual irregularities. At present, T. quinquecostatus is used only for ornamental and ground cover purposes. A literature search was conducted to retrieve information regarding the essential oil composition and biological properties of T. quinquecostatus from PubMed, Science Direct, Wiley, Springer, Taylor and Francis, Wiley, and other literature databases. T. quinquecostatus can be divided into different chemotypes, such as γ-terpinene, thymol, phenol, carvacrol, and geraniol, according to the presence of major components in its essential oil. Further, the essential oil from T. quinquecostatus has been reported to possess various therapeutic properties such as antioxidant, antimicrobial, anticancer, anti-inflammatory, analgesic, sleep prolonging, soothing, skin protection and whitening, anti-aging, anti-obesity, and anti-acne properties. In conclusion, this review will be helpful for utilizing the T. quinquecostatus plant in different industries including food, pharmaceuticals, pesticides, perfumery, and cosmetics.